Lian Hua Qing Wen : perannya pada terapi COVID-19 - Vidor, Marco; Lawrensia, Sherly (Cermin Dunia Kedokteran, 2021)
Pandemi COVID-19 belum berakhir. Berbagai studi mengenai terapi COVID-19 masih terus berjalan. Peran Traditional Chinese Medicine (TCM) sebagai salah satu adjuvan terapi COVID-19 masih kontroversial. Lian Hua Qing Wen sebagai salah satu jenis TCM, berpotensi menjadi salah satu adjuvan pada terapi COVID-19.COVID-19 pandemic is still ravaging. Studies are being conducted to determine the best therapeutic option for COVID-19. The role of Traditional Chinese Medicine (TCM) as an adjuvant therapy for COVID-19 is still controversial. As one of the TCM, Lian Hua Qing Wen may have a role as an adjuvant to COVID-19 treatment.